Work-related psychosocial factors and working life expectancy among Finnish public sector employees aged 50 years or older - Haukka, Eija; Heikkilä, Katriina; Pentti, Jaana; Vahtera, Jussi; Chungkham, Holendro Singh; Zaninotto, Paola; Kivimäki, Mika; Ervasti, Jenni; Stenholm, Sari (Nordic Association of Occupational Safety and Health NOROSH, 2026)
Objective
This study aimed to examine the associations between work-related psychosocial factors and working life expectancy (WLE) across occupational groups among Finnish public sector employees aged ≥50 years.
Methods
In this cohort study, 70 662 Finnish public sector employees completed surveys on work-related psychosocial factors in 2000–2002, 2004, 2008, 2011–2012, 2013–2014, and 2015–2016, with each participant responding at least once at age ≥50 years (response rates 66–71%; 80% female). Survey data were linked to pensionable earnings records to verify work participation until 31 December 2018. WLE WLE between ages 50 and 68 was estimated using a multi-state life tables approach. Analyses were conducted among three occupational groups: managers and specialized professionals, non-manual professionals, and service and manual workers.
Results
The overall WLE at age 50 was 13.1 years [95% confidence interval (CI) 13.1–13.2]. Work-related psychosocial factors were associated with shorter WLE across all occupational groups, with WLE shortening from the highest to the lowest occupational group. High effort–reward imbalance (ERI) was associated with the shortest WLE, approximately five months shorter than among employees with low ERI. Compared with managers and specialized professionals with low psychosocial risks, high ERI, high job strain, high relational or procedural injustice were each associated with an approximately 1-year shorter WLE among service and manual workers. Occupational group showed a stronger association with WLE than the accumulation of psychosocial risk factors. No sex differences in WLE were observed.
Conclusion
These findings suggest that promoting favorable psychosocial working conditions may extend working careers and reduce inequalities in working life participation, particularly among service and manual workers.